Specification and uses of econometric models - Brown, Tillman Merritt (London, Macmillan; New York, St. Martin's P., 1970)
As one of the bold attempts to construct a general-purpose macroeconomic in a general equilibrium framework and use it econometrically for questions of policy , this book provides a very interesting standpoint.
includes index
Bibliography: p. [463]-468.
occ 17/01/2019
Loans
Keywords: Econometrics; Economics - mathematical methods